Insights into plasmon-assisted chemical reactions: From fabrication to characterization - Juan Xu; Xinwei Huang; Jing Peng; Shunxing Li; Jian-Feng Li (eScience)
The integration of surface plasmons with catalysis has opened a new frontier in the field of chemical energy conversion, offering unprecedented opportunities for enhancing reaction activity and selectivity. This review delves into the optical properties of plasmonic materials, the intricate mechanisms of plasmon-assisted chemical reactions (PACRs), and the fabrication of plasmonic catalysts, highlighting the significance of the structure–performance relationship. The mechanisms of PACRs are summarized to understand their synergistic contributions to reactions. The review further examines modern experimental strategies for characterizing surface plasmon resonance properties, including scanning probe microscope, in situ spectroscopy, and ultrafast laser pump-probe techniques, which provide real-time, dynamic insights into molecular interactions and structural changes with high spatial and temporal resolution. We conclude by outlining the challenges and future prospects for PACRs, emphasizing the need for innovative strategies to fully exploit the potential of PACRs for sustainable energy conversion and environmental remediation.